The Influence of the Service Process on Service Quality: A Study of BPJS PROLANIS Patients at Prodia Clinic Jambi - Adam Permana Yudha; Boni Saputra (Jurnal Ilmu Administrasi Negara AsIAN (Asosiasi Ilmuwan Administrasi Negara), 2026)
The quality of healthcare services is a key indicator of the success of the National Health Insurance (JKN) system; however, the expansion of BPJS Kesehatan enrollment has not been fully accompanied by equitable service quality, as reflected by the gap in perceptions at the Prodia Clinic in Jambi, where 47% of PROLANIS patients rated the empathy aspect of service as only "fair," even though Standard Operating Procedures had been implemented. This study aims to analyze the influence of service processes on the quality of care for BPJS PROLANIS patients at the Prodia Clinic in Jambi. The study employed an associative quantitative approach, using simple random sampling of 99 patients from a population of 5,000, and a validated instrument measuring seven service process indicators and six dimensions of service quality, analyzed via simple linear regression in SPSS 26. The results showed that both service processes and service quality fell into the "good" category (TCR 80% and 79%), with the regression equation Y = 10.244 + 0.724X, calculated t = 8.923 > critical t = 1.984, significance 0.000 (p < 0.05), and coefficient of determination R² = 0.451. These findings underscore the importance of strengthening communication effectiveness and the consistency of service safety procedures at Prodia Clinic Jambi to improve the quality of service for BPJS PROLANIS patients continuously.